Prevalence, characteristics and mortality outcomes of obese, nonobese and lean NAFLD in the United States, 1999–2016. (22nd April 2020) - Zou, B.; Yeo, Y. H.; Nguyen, V. H.; Cheung, R.; Ingelsson, E.; Nguyen, M. H.
Abstract: Background: Updated prevalence and outcome data for nonobese NAFLD for the multi‐ethnic US population is limited. Objectives: We aimed to investigate the prevalence, clinical characteristics and mortality of obese and nonobese individuals with NAFLD in the United Sates. Methods: A retrospective study was conducted using the 1999–2016 NHANES databases. We determined hazard ratio stratified by obesity status in NAFLD individuals using Cox regression and log‐rank test. Results: Overall NAFLD prevalence was 32.3%: 22.7% were obese and 9.6% were nonobese, with increasing trend over time for obese NAFLD, but not nonobese NAFLD. Amongst those with NAFLD, 29.7% (95% CI: 27.8%‐31.7%) were nonobese, of which 13.6% had lean NAFLD. Nonobese NAFLD was more common in older (40.9% if ≥ 65 vs. 24.2% if < 65 years), male (34.0% vs. 24.2%) and foreign‐born Asian people (39.8% vs. 11.4%) and uncommon in black (11.5% vs 30–35% in other ethnicities, P < 0.001). Metabolic comorbidities were common in nonobese NAFLD individuals who also had more advanced fibrosis. Nonobese NAFLD individuals had higher 15‐year cumulative all‐cause mortality (51.7%) than obese NAFLD (27.2%) and non‐NAFLD (20.7%) ( P < 0.001). However, DM and fibrosis, but neither obese nor nonobese NAFLD compared to non‐NAFLD was independently associated with higher mortality. Conclusion: Nonobese NAFLD makes up about one‐third of the NAFLD in the United States (even higher in older, male and foreign‐born individuals) and carries higher mortality than obese NAFLD. Screening for NAFLD should be considered in high‐risk groups even in the absence of obesity. Abstract :